Combined nutritional and frailty screening improves assessment of short-term prognosis in older adults following percutaneous coronary intervention. Issue 3 (9th May 2023) - Mangalesh, Sridhar; Daniel, Kevin Varughese; Dudani, Sharmila; Joshi, Ajay
Abstract : Background: Frailty and malnutrition are well-known factors influencing outcomes of myocardial infarction (MI) in older adults. Due to considerable overlap between both entities, whether the simultaneous assessment of frailty and nutrition adds nonredundant value to risk assessment is unknown. Methods: We performed a prospective cohort study on 402 patients aged at least 65 years diagnosed with ST-elevation MI that underwent percutaneous coronary intervention. Nutritional status was assessed by Controlling Nutritional Status score (CONUT), Prognostic Nutritional Index, and Geriatric Nutritional Response Index. Frailty was assessed by Clinical Frailty Scale (CFS), Derby frailty index, and acute frailty network. Primary outcome was major adverse cardiac events (MACE), comprising all-cause mortality, non-fatal MI, and unplanned repeat revascularization during 28-day follow-up. Increment in Global Registry of Acute Coronary Events (GRACE) score performance following the addition of nutrition and frailty was assessed. Results: The incidence of MACE was 8.02 (6.38–9.95) per 1000 person-days. The CONUT score and CFS were the best predictors of MACE and independent predictors in the multivariate Cox-regression models [hazard ratios, 2.80 (1.54–5.09) and 2.54 (1.50–4.29)]. CONUT score classified 151 (37.6%) patients as malnourished, and CFS classified 131 (32.6%) as frail. The addition of both CONUT and CFS to the GRACE score led to better model discrimination and calibration through improved c-statistic (+0.165) ( P < 0.0001) and Akaike and Bayesian information criteria. Conclusion: Combining CONUT and CFS provides nonredundant prognostic value despite their overlapping nature. Combined nutritional and frailty screening may improve risk prognostication in older adults following MI.